An OOP MATLAB Extensible Framework for the Implementation of Genetic Algorithms. Part II: Case Study. (2015) - Razvan, Cazacu; Lucian, Grama; Ioan, Mocian
Abstract: This paper presents a case study to illustrate certain details, the ease of implementation and optimization efficiency of the OOGA library, an object oriented framework for the implementation of genetic algorithms in MATLAB. The chosen example is a benchmark problem for the structural size optimization of a plane truss. The plane truss is analyzed with the help of classes for parametric definition and FEA simulation incorporated in OOGA. Three different mutation operators are used and compared and the results are further compared with the ones obtained in other studies. As shown, the OOGA library is capable of performing optimization with GA in an efficient manner, its flexibility and extensibility allowing the researcher to easily implement and incorporate any new component.